2013
DOI: 10.1080/19440049.2013.837586
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the occurrence of photo-initiators and amine synergists in cartonboard packaging on the German market and their migration into the packaged foodstuffs

Abstract: In  a surveillance study from 2008 to 2011, in total 310 food products, predominately packed in cartonboard, were collected from the German market. First, the packaging materials were analysed for their content of six photo-initiators and five amine synergists by high-performance liquid chromatography with diode array detection (HPLC-DAD). If high amounts of these substances were detected, subsequently the foodstuffs were analysed by means of HPLC-MS or tandem MS, respectively. Benzophenone (BP) was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 11 publications
3
49
4
Order By: Relevance
“…Theoretically, the PIs in the UV curable resins, food contact materials and other products in households can migrate into indoor dust by evaporation and abrasion processes, since PIs are usually of low molecular weights and are not fully incorporated into the polymer network. 3 The present study demonstrated the occurrence of PIs in indoor dust, and plausible human exposure to PIs through dust ingestion. As illustrated in Figure 2 and Table S8, almost all the target PIs could be positively identified in the indoor dust samples, except for Irgacure 369 and 2-Cl-TX.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Theoretically, the PIs in the UV curable resins, food contact materials and other products in households can migrate into indoor dust by evaporation and abrasion processes, since PIs are usually of low molecular weights and are not fully incorporated into the polymer network. 3 The present study demonstrated the occurrence of PIs in indoor dust, and plausible human exposure to PIs through dust ingestion. As illustrated in Figure 2 and Table S8, almost all the target PIs could be positively identified in the indoor dust samples, except for Irgacure 369 and 2-Cl-TX.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…1 With regard to molecular structures, the most frequently used PIs can be categorized as benzophenones (BZPs), thioxanthones (TXs), and amine co-initiators (ACIs). 2,3 These compounds are mainly applied in light sensitive materials such as ultraviolet (UV) curable ink, coating and adhesive, which are employed in a variety of applications including printing inks, overprint varnishes, primers, pigmented paints, clear topcoats, and bonding for abrasives, encapsulates and pressure sensitive adhesives. 4 The wide use of PI additives has triggered increasing awareness of their potential adverse effects on biota and humans.…”
Section: ■ Introductionmentioning
confidence: 99%
“…29 They used the first method to determine Irgacure 907 s , ITX and ethyl-4-(dimethylamino)benzoate) (EDB) in yoghurt samples. The extraction procedure was the same as described by Rothenbacher et al, 14 with slight differences to improve extraction.…”
Section: Liquid Chromatography (Lc)mentioning
confidence: 99%
“…29 The method used to extract these photoinitiators from the FCM was that proposed by Pastorelli et al 16 Chromatographic separation was achieved with a reversed-phase C18 column (Purospher s Star RP 18e: i.d., 250 mmÂ4 mm and particle size, 5 mm) and a mobile phase composed by water and acetonitrile, in gradient mode. This method yielded good resolution, but the time required for the analysis was 70 min.…”
Section: Liquid Chromatography (Lc)mentioning
confidence: 99%
See 1 more Smart Citation